Removal of a retained intracardiac radiolucent guidewire fragment using an Atrieve™ vascular snare using combined fluoroscopy and transesophageal echocardiography guidance in an infant - Asif Padiyath; Eudice E Fontenot; Boban P Abraham (Wolters Kluwer Medknow Publications, 2017)
Retained intravascular foreign body is a well-known complication of central venous access placement in children as well as adults. Most of these foreign bodies are radio-opaque and hence are removed under fluoroscopy guidance. In our case, we describe the removal of an intracardiac radiolucent foreign body in an infant utilizing a combination technique - transesophageal echocardiogram and fluoroscopy.